Financial Freedom: Pathways and Challenges to Economic Empowerment (Pravaha, 2025)
Financial freedom has become a crucial element of individual well-being and sustainable economic progress in today’s world. It goes beyond the conventional focus on accumulating wealth, instead highlighting the importance of financial independence, adaptability, and the freedom to make choices without being limited by economic barriers. This concept paper delves into the various aspects of financial freedom by exploring its sources, forms, and broader socio-economic relevance. It draws on theoretical frameworks such as the Life-Cycle Hypothesis and Financial Capability Theory and integrates empirical insights on how financial literacy, digital financial tools, and socio-economic conditions influence financial freedom. The paper pays particular attention to the situation in developing countries like Nepal, where obstacles such as irregular income, insufficient financial education, and gender inequality continue to hinder progress. Relying on a qualitative approach and secondary data, the paper proposes practical strategies to promote inclusive financial empowerment. These include improving financial education, encouraging income diversification, broadening access to financial services, and filling existing policy gaps. Ultimately, financial freedom is not just a personal milestone but a shared objective that can strengthen economic resilience, enhance mental health, and support sustainable development.